The Concept of “Indian Philosophy” as a Product of Intercultural Dialogue (Wilhelm Halbfass’s India and Europe Revisited ) (Politeja, 2016)
This paper is a sequel to another paper of the same author: “Some Marginal Notes on [W. Halbfass’s] India and Europe” (in: E. Franco, K. Preisendanz (eds.), Beyond Orientalism. The Work of Wilhelm Halbfass and its Impact on Indian and Cross‑Cultural Studies, Amsterdam–Atlanta 1997). In the present paper the concept of “Indian philosophy” is discussed – with references to the analysis of the concept in the book India and Europe by W. Halbfass. The central idea of the paper is this: “Indian philosophy” is not a kind of primordial entity it is often said to be, but rather a contingent concept which gradually evolved in the 19th and 20th century in the process of intercultural interaction between Indian (South Asian) and European (Western) intellectual traditions.